2018
DOI: 10.1088/1741-2552/aad7b1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reshaping of functional brain networks during visual object recognition

Abstract: We speculate that these observations are applicable not only to other fast cognitive functions but also to detect fast disconnections that can occur in some brain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…More essentially, scalp analysis does not allow making inferences about interacting brain regions. A potential solution is an emerging technique called "MEG/EEG source connectivity" (De Pasquale et al, 2010;Hipp et al, 2012;Mehrkanoon et al, 2014;Hassan et al, 2015;Kabbara et al, 2017;Mheich et al, 2017;Kabbara et al, 2018;Rizkallah et al, 2018), which reduces the aforementioned volume conduction. It is also conceptually attractive since networks can be directly identified at the cortical level with a high time/space resolution (for more details, see .…”
Section: Introductionmentioning
confidence: 99%
“…More essentially, scalp analysis does not allow making inferences about interacting brain regions. A potential solution is an emerging technique called "MEG/EEG source connectivity" (De Pasquale et al, 2010;Hipp et al, 2012;Mehrkanoon et al, 2014;Hassan et al, 2015;Kabbara et al, 2017;Mheich et al, 2017;Kabbara et al, 2018;Rizkallah et al, 2018), which reduces the aforementioned volume conduction. It is also conceptually attractive since networks can be directly identified at the cortical level with a high time/space resolution (for more details, see .…”
Section: Introductionmentioning
confidence: 99%
“…An atlas-based approach was used to project EEG signals onto an anatomical framework consisting of 68 cortical regions identified by means of the Desikan-Killiany atlas (Desikan et al, 2006). To reconstruct the regional time series, we used the weighted Minimum Norm Estimate (wMNE), widely used in the context of EEG source localization (Gramfort et al, 2012;Hassan et al, 2015;Hauk, 2004;Kabbara et al, 2017;Rizkallah et al, 2018) and showed higher performance than other algorithms in several comparative studies (Hassan et al, 2014;Hassan et al, 2016). The regional time series were then filtered in the different EEG frequency bands: Delta [0.5-4 Hz], Theta [4][5][6][7][8], alpha [8][9][10][11][12][13], beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]…”
Section: Estimation Of Regional Time Seriesmentioning
confidence: 99%
“…Electrode impedances were kept below 20 kOhm. EEG signals are frequently contaminated by several sources of artifacts, which were addressed using the same preprocessing steps as described in several previous studies dealing with EEG resting-state data (Kabbara et al, 2017;Kabbara et al, 2018;Rizkallah et al, 2018). Briefly, bad channels (signals that are either completely flat or contaminated by movement artifacts) were identified by visual inspection, complemented by the power spectral density.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%
“…Dynamic brain networks were reconstructed using the "EEG source connectivity" method , combined with a sliding window approach as detailed in (Kabbara et al, 2017;Kabbara et al, 2018;Rizkallah et al, 2018). "EEG source connectivity" involves two main steps: i) solving the EEG inverse problem in order to estimate the cortical sources and reconstruct their temporal dynamics, and ii) measuring the functional connectivity between the reconstructed time-series.…”
Section: Dynamic Brain Network Constructionmentioning
confidence: 99%
See 1 more Smart Citation